Relationship Between Diaphragm Function and Sarcopenia Assessed by Ultrasound: A Cross-Sectional Study - Takahiro Shinohara; Toru Yamada; Shuji Ouchi; Suguru Mabuchi; Ryoichi Hanazawa; Kazuharu Nakagawa; Kanako Yoshimi; Tatsuya Mayama; Ayane Horike; Kenji Toyoshima; Yoshiaki Tamura; Atsushi Araki; et al. (Diagnostics)
Background/Objectives: The diaphragm is important for respiration, but the effects of age-related muscle loss and sarcopenia on diaphragm function are unclear. We evaluated the associations of sarcopenia and skeletal muscle mass (SMM) with diaphragm function. Methods: This study was conducted at three Japanese hospitals from May 2023 to September 2024. The participants underwent bioelectrical impedance for SMM assessment, as well as pulmonary function tests. Diaphragm ultrasound was used to measure the thickness at functional residual capacity (FRC), thickening fraction (TF), and diaphragm excursion (DE) during deep breathing (DB), and their associations with sarcopenia and low skeletal muscle index (SMI) were analyzed. Results: Overall, 148 patients (mean age 78.1 years; sarcopenia, n = 35; non-sarcopenia, n = 103) were included. No statistically significant differences in thickness(FRC), TF and DE were observed between the sarcopenia group and the non-sarcopenia group. The low SMI group had significantly lower thickness (difference −0.22, 95% CI; −0.41, −0.29) and DE (difference −9.2, 95%CI; −14.0, −4.49) than the normal SMI group. Multivariable linear regression analyses adjusted for age, sex, and stature revealed no association between thickness (FRC) and sarcopenia (p = 0.98), but thickness (FRC) was negatively associated with low SMI (p = 0.034). DE during DB was negatively associated with sarcopenia (p = 0.024) and low SMI (p = 0.001). TF showed no associations. Conclusions: DE during DB was reduced in patients with sarcopenia and low SMI, and thickness (FRC) was reduced in those with low SMI without sarcopenia.